Respostas

2013-12-16T09:52:22-02:00
A) 13² = 13 .13 = 169

b) 2² = 2 . 2 = 4

c) x² + 11² = x . x + 11 . 11 = x + 121 = 121x

d) 5a² + b² = 5a . 5a + b . b = 10a + b = 10ab

e) 3² = 3 . 3 = 9

f) ( 9 - x ) . ( 9 - x) = 81 - 9x - 9x + x²=
 x² - 18x + 81 = 0
a= 1
b= -18
c= 81
x= - ( - 18) + - V -18² - 4 . 1 . 81 / 2 . 1
x= 18 + - V 324 - 324 / 2
x = 18 + - V 0 /2
x' e x" = 18 + 0 / 2 = 18/ 2 = 9

g) ( a - 6b) . ( a - 6b) = a² - 6ab - 6ab + 36b² = a² - 12ab + 36b²

h) ( 2a - b ) . ( 2a - b) = 4a² - 2ab - 2ab + b² = 4a² + b² - 4ab 

i) 4 - 10b + 10b - 25b² = 4  - 25b²

j) 16 - 4b + 4b - b² = 16 - b²

1 5 1